2023
DOI: 10.20944/preprints202303.0058.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does ESG Impact a Firm’s Sustainability Performance? The Mediating Effect of Firm Innovation Performance

Abstract: In this age of global warming, academics and policymakers are increasingly concerned about firm environmental sustainability success. Therefore, this study aims to investigate whether Environmental, Social and Governance (ESG) performance impacts sustainability performance through the mediating effect of firm innovation. To this end, Structural Equation Modeling (SEM) was deployed to analyze data collected from the employees of manufacturing industries in an emerging economy like Bangladesh. The results reveal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 142 publications
0
0
0
Order By: Relevance
“…Darmayoga et al (2020) found that Indonesian mining companies' environmental accounting disclosures are strong enough to mediate the consequences of environmental performance on company value. Zhou et al, (2023) analyzed Bangladeshi manufacturing companies and found that companies' innovation performance fully mediates the relationship between sustainability performance and environmental social, and governance initiatives. Financial information disclosure is made concisely to comply with standards, rules, and regulations.…”
Section: Significance Of Environmental Accounting Disclosure Practice...mentioning
confidence: 99%
See 1 more Smart Citation
“…Darmayoga et al (2020) found that Indonesian mining companies' environmental accounting disclosures are strong enough to mediate the consequences of environmental performance on company value. Zhou et al, (2023) analyzed Bangladeshi manufacturing companies and found that companies' innovation performance fully mediates the relationship between sustainability performance and environmental social, and governance initiatives. Financial information disclosure is made concisely to comply with standards, rules, and regulations.…”
Section: Significance Of Environmental Accounting Disclosure Practice...mentioning
confidence: 99%
“…These relationships represent the mediating role of environmental accounting disclosure practices between the disclosure aspects (financial and non-financial) and sustainable development. However, other studies (for example, Monteiro et al (2023), Zhou et al (2023), andAli et al (2022)) use environmental accounting disclosure as a mediating variable to explore the relationship between financial disclosure, non-financial disclosure, and sustainable development. To further extend the knowledge on environmental accounting disclosure and fill the research gap, this study also examines the mediating effect of environmental accounting disclosure practices between financial and non-financial disclosures and sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…According to the theory of sustainable development, the long-term health of a company determines its performance, which is closely related to its ESG performance. Drawing on the theory of Zhou et al, in the past economic development, agricultural entities expanded scale and increased production at the expense of the environment, which caused irreparable harm to the local environment [55]. At a time when more and more attention is being paid to the environment, drawing on the ideas of Chen et al, the main body of agricultural management should transform in the direction of sustainable development without reducing the output in order to meet the call of the state, comply with the development law of green economy, and complete the perfect transformation of the new era [56,57].…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%